Morphology and ultrastructure of the Dufour gland of Myzinum sp (Tiphiidae) - Billen, Johan; Lopes Justino, Cintia Eleonora [UNESP]; Carnimeo, Fernando Henrique [UNESP]; Noll, Fernando Barbosa [UNESP] (Pensoft Publ, 2017)
The Dufour gland of two Myzinum females was studied with light and electron microscopy, and is formed by a large sac lined with a monolayered secretory epithelium. The epithelium displays a crenellate appearance, which is the result of the peculiar shape of the secretory cells, that have a cupola-like central portion and a more flattened appearance in the contact region with other cells. The ultrastructural organization is indicative for the elaboration of a non-proteinaceous secretion. The gland opens ventrally to the sting base, but does not open through the sting, as does the venom gland duct. The sting itself is dorsally curved, which may be a functional adaptation to facilitate stinging large beetle larvae from above, as these are the common hosts for tiphiid wasps.
Keywords: Morphology; ultrastructure; Dufour gland; curved sting; Myzinum; Tiphiidae